Corrigendum - Agrivita Agrivita (AGRIVITA, Journal of Agricultural Science, 2021)
Corrigendum to “Effects of Foliar Application Chitosan and Salicylic Acid on Physiological Characteristics and Yield under Deficit Irrigation Condition” [AGRIVITA Journal of Agricultural Science, 43(1), 101-113]